Women’s empowerment and its effect on community development in Oman: predictive model and indicators for best practices - Amzat, Ismail Hussein; Al-Ani, Wajeha Thabet Khadem; Ismail, Omer Hashim; al Omairi, Turkiya (2019)
ABSTRACT This study investigates the level of women’s empowerment in Omani society from the point of view of female university students from three public universities with respect to educational opportunity, equality in employment and their social status in the community. The study proposes a model for how to empower women based on the perceptions of university females and the factors that must be considered for improving the status of women in Oman. The model also provides indicators for social and community practices using confirmatory factor analysis and Path Analysis to determine pertinent factors and their effects on women’s development. The results showed a strong direct effect of women’s empowerment in Oman on community development. Despite the latest developments in Oman, as long as cultural rigidity remains, tradition upholds a conservative viewpoint of women, and families adhere to their uncompromised principles, women will remain subordinated by these factors according to the viewpoint of participants. This study concludes with recommendations for further research, including enrolment of females in all areas of specialisation creating more job opportunities for women, encouraging women’s leadership, and additional education of women’s rights and needs.